Confirming the Constructs of Adlerian Personality Priority Assessment. (3rd July 2019) - Dillman Taylor, Dalena; Bratton, Sue C.; Henson, Robin K.
Abstract: A split-sample cross-validation confirmatory factor analysis ( N = 1, 210) confirmed the 4-factor structure of the Adlerian Personality Priority Assessment (APPA) with 2 distinct subsamples. Discriminant validity, prevalence rates of priorities, and preliminary group norms are reported.